Features of measurement of an atmospheric precipitation at the Ukrainian Antarctic station Academician Vernadsky - S. V. Klok (Ukrainian Antarctic Journal, 2010)
Results of measurements of atmospheric precipitation at the Ukrainian Antarctic station Academician Vernadsky are analyzed. The comparative analysis of these data from average, and also by data of calculations by results of supervision over accumulation of a snow and a stock of a moisture in a snow in the given area is lead. The received results testify to essential losses at direct measurements of deposits at station. Possible approaches on elimination of the given problem are offered.